Pengaruh Rasio Keuangan Terhadap Harga Saham Perbankan - Riyadi, Selamet; Iqbal, Muhammad (Jurnal Ilmu Manajemen, 2024)
The aim of this research is to analyze the influence of financial ratios in this case Earning Per Share, Price Earning Ratio, Net Profit Margin, Price Book Value and Debt to Equity Ratio on banking share prices included in KBMI 3 and 4 for the period 2017 to 2021. Methodology The research used uses data taken from various sources such as the Indonesian Stock Exchange, Yahoo Finance and the Mirae Asset Application. The data collected was then processed using the IBM SPSS Statistics 22 application. The research results showed that the financial ratio variables consisted of Earning Per Share (EPS), Price Earning Ratio (PER), Net Profit Margin (NPM), Price Book Value (PBV), Debt to Equity Ratio (DER) simultaneously influences the share prices of banking companies that are included in the KBMI 3 and 4 categories on the Indonesian Stock Exchange. Meanwhile, partially the only thing that has a significant effect on the dependent (dependent) variable is Earning Per Share. Other variables such as Price Earning Ratio (PER), Net Profit Margin (NPM), Price Book Value (PBV) and Debt to Equity Ratio (DER) partially have no effect on banking company share prices.